Temporal trend of cases of death from acute myocardial infarction in Santo Antônio de Jesus - BA between the years 2016 to 2020 (Research, Society and Development, 2022)
This study was structured with the objective of analyzing the mortality rates due to acute myocardial infarction in the Municipality of Santo Antônio de Jesus - Bahia between the years 2016 to 2020. It is an epidemiological, temporal and descriptive study. Data were obtained from a secondary database referring to mortality from AMI, in the SUS Mortality Information System, made available by the Information Technology department of the Unified Health System. The following variables were evaluated: sex, color/race, age group and by place of occurrence in a time frame from 2015 to 2019. The total number of deaths from AMI was 134 cases, predominantly male (54.5%); non-white color (75%); in the elderly age group (70.1%) and in the hospital environment (64.4%). We emphasize the need for government implementation and investment in terms of public policies aimed at the prevention and promotion of cardiovascular diseases. Therefore, the epidemiological trend shows that the highest rates of deaths from AMI are male, non-white, elderly and in the hospital environment.